Racing with superior and inferior team-members: an experimental test of effort changes in a cycling team sprint - Haugen, T.; Pels, F.; Stålesen Gysland, T.; Hartvigsen, F. K.; Høigaard, R. (International Journal of Sport and Exercise Psychology, 2021)
The study purpose was to investigate the effect of ability on effort within a sport-specific conjunctive task. The hypothesis was that, compared to working alone, inferior team members would increase their effort when performing a conjunctive sport task in a three-person team, whereas superior team members would decrease their effort. Participants were randomly assigned to one of three experimental conditions (inferior member, control member or superior member) during a 1-min maximal team time trial on a stationary bike. One hundred five relatively well-trained undergraduate sports students (male = 64, female = 41) performed 1-min maximum ergometer cycling tests individually and in random three-person teams. After completing the individual test, participants were told that the next trial would be performed in teams with a conjunctive task structure and were randomly assigned to receive manipulated feedback (that they were either the inferior member or the superior member). Control members received no feedback. Participants in the inferior member condition showed a statistically significant performance gain (i.e., effort gains) when performing the test with stronger partners. Participants in the control and superior member conditions showed neither performance gains nor performance losses (i.e., no effort losses) when completing the test within teams. Receiving feedback about being the inferior member of a sports team may lead to increased effort and, thus, improved performance (i.e., the Köhler effect), whereas no evidence of a free-rider effect was identified in the superior members.